Exploring the Correlation between Students’ Perception of Translanguaging and Willingness to Communicate: A Mixed-Methods Study - Zam, Fakhruddin Zam; Nurhayati, Lusi; Ashadi, Ashadi (JOLLT Journal of Languages and Language Teaching, 2025)
Translanguaging offers potential significance in assisting EFL studentsâ€™ engagement in L2 communication, making it valuable to investigate whether studentsâ€™ perception of translanguaging correlates with their willingness to communicate in a second language. This mixed-methods study explores the relationship between studentsâ€™ perception and L2 willingness to communicate in classroom communicative settings. 65 participants from two universities enrolled in an English education program participated in this study. The quantitative data were collected using 5-Likert scale questionnaires and qualitative data through in-depth interviews with subset participants. The quantitative data, including descriptive statistics, correlation, and regression analysis, were formulated in SPSS 26. Meanwhile, the interviews were analyzed using thematic analysis. The findings showed that studentsâ€™ perception of translanguaging correlates significantly and positively to their L2 WTC (r = .587). Based on the qualitative data, key themes related to the significance of translanguaging, such as facilitation of understanding, self-confidence improvement, reduced anxiety, and promotion of a positive classroom environment emerged as factors contributing to the studentsâ€™ increased L2 WTC. These findings suggest that studentsâ€™ perception of translanguaging influences their attitudes toward L2 communication, leading to a decreased or increased WTC level. Thus, translanguaging should be encouraged as an alternative strategy in L2 classrooms to enhance communication in EFL settings, particularlyÂ by maximizing L2 understanding and fostering an emotionally safe learning environment.Â